2008
DOI: 10.1111/j.1550-7408.2008.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Lineage of Closely Related Trypanosomes (Trypanosomatidae, Kinetoplastida) of Anurans and Sand Flies (Psychodidae, Diptera) Sharing the Same Ecotopes in Brazilian Amazonia1

Abstract: Analysis of the phylogenetic relationships among trypanosomes from vertebrates and invertebrates disclosed a new lineage of trypanosomes circulating among anurans and sand flies that share the same ecotopes in Brazilian Amazonia. This assemblage of closely related trypanosomes was determined by comparing whole SSU rDNA sequences of anuran trypanosomes from the Brazilian biomes of Amazonia, the Pantanal, and the Atlantic Forest and from Europe, North America, and Africa, and from trypanosomes of sand flies from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 41 publications
4
91
0
23
Order By: Relevance
“…DNA from Leishmania-related parasites capable of infecting sand flies, such as Endotrypanum (Kato et al, 2007) and anuran Trypanosoma species (Ferreira et al, 2008), and also DNA from the sand flies Phlebotomus papatasi and Lutzomyia ayacuchensis, were included to evaluate the present LAMP primer specificity.…”
Section: Dna Preparationmentioning
confidence: 99%
“…DNA from Leishmania-related parasites capable of infecting sand flies, such as Endotrypanum (Kato et al, 2007) and anuran Trypanosoma species (Ferreira et al, 2008), and also DNA from the sand flies Phlebotomus papatasi and Lutzomyia ayacuchensis, were included to evaluate the present LAMP primer specificity.…”
Section: Dna Preparationmentioning
confidence: 99%
“…The first evidence of the transmission of snake trypanosomes by sand fl ies was described by Viola et al (13) , who identifi ed trypanosomes from Viannamyia tuberculata that had approximately 94% similarity to a trypanosome isolated from Crotalus durissus. Furthermore, some sand fl ies have been infected by Trypanosoma species acquired from amphibians (14) . However, the identifi cation of the trypanosomes in this study requires further confi rmation, because sequence analysis showed identity values <90%.…”
mentioning
confidence: 99%
“…De início, sanguessugas aquáticas eram os únicos vetores reconhecidos (Simpson et al, 2006). Posteriormente, infecções experimentais comprovaram a participação de outros vetores, como mosquitos, flebotomíneos e culicoides (Simpson et al, 2006;Hamilton et al, 2007;Ferreira et al, 2007Ferreira et al, , 2008. (Noyes et al, 1999;Stevens et al, 2001;Hamilton et al, 2004;Simpson et al, 2006;Fermino et al, 2015).…”
Section: Clado Aquáticounclassified
“…Sequências do gene ribossômico têm sido bastante utilizadas para inferir relações filogenéticas entre organismos da classe Kinetoplastida Simpson et al, 2006;Lukes et al, 2014;Cavalier-Smith, 2016), para estabelecer os principais grupos naturais dentro da família Trypanosomatidae Merzlyak et al, 2001;Cavazzana et al, 2010) e para a identificação de gêneros, espécies, linhagens e genótipos dentro do gênero Trypanosoma (Maia da Silva et al, 2004;Rodrigues et al, 2006;Hamilton et al, 2007;Ferreira et al, 2007Ferreira et al, , 2008Viola et al 2008;Lemos et al, 2015;Austen et al, 2016). …”
Section: Gene Ribossômico (Rdna)unclassified